Investigation of vibration protection system of a seat with quasi-zero stiffness under stochastic effects on the elements of running equipment of a motor grader - M. S. Korytov; V. S. Shcherbakov; I. E. Kashapova (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
With the help of a complex simulation mathematical model of a motor grader developed in the Matlab environment, including subsystems of vibration-protective cab supports, a vibration-protective mechanism of the operator's seat, setting stochastic effects on the elements of running equipment when moving along a microrelief, a computational experiment is carried out, when processing the results of which, the influence of a number of system parameters on the root-mean-square seat acceleration deviation in the vertical direction. The variable parameters are the root mean square deviation of the vertical coordinates of the microprofile of the supporting surface, the speed of motion of the motor grader, the size of the zone of quasi-zero stiffness of the vibration protection mechanism of the operator's seat, the value of the increase in the spring stiffness coefficient of the vibration protection mechanism, which sets the slope of the average section of the static power characteristic of the vibration protection mechanism. An increase in the size of the zone of quasi-zero stiffness allows several times to reduce the average value of the root-mean-square deviation of the seat acceleration for a set of movements at various profile heights and speeds. Giving the middle part of the static characteristic a small slope also allows a slight decrease in the average value of the standard deviation of the seat.